2016
DOI: 10.1172/jci89031
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy vitamin D status and risk of preeclampsia

Abstract: Quebec Breast Cancer Foundation and Genome Canada Innovation Network. This trial was funded by the National Heart, Lung, and Blood Institute. For details see Acknowledgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
165
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 58 publications
8
165
2
10
Order By: Relevance
“…Nevertheless, the number of subjects in the Cochrane review to determine the risk of preeclampsia was too limited (n = 293) for a disease of such prevalence. However, other meta-analyses of interventional studies [53,54] and a further randomized control trial (RCT; VDAART study) [57] with more participants than in the previous meta-analysis, did not support previous results. The VDAART study (Vitamin D Antenatal Asthma Reduction Trial) in the United States including 408 placebo and 408 subjects receiving 4,400 UI vitamin D3 initiated early in pregnancy (10-18 weeks), did not find a reduction on the preeclampsia incidence (8.08 vs. 8.33%, respectively; relative risk (RR) 0.97; 95% CI 0.61-1.53) [57].…”
Section: Vitamin D Supplementation and Preeclampsia Riskcontrasting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, the number of subjects in the Cochrane review to determine the risk of preeclampsia was too limited (n = 293) for a disease of such prevalence. However, other meta-analyses of interventional studies [53,54] and a further randomized control trial (RCT; VDAART study) [57] with more participants than in the previous meta-analysis, did not support previous results. The VDAART study (Vitamin D Antenatal Asthma Reduction Trial) in the United States including 408 placebo and 408 subjects receiving 4,400 UI vitamin D3 initiated early in pregnancy (10-18 weeks), did not find a reduction on the preeclampsia incidence (8.08 vs. 8.33%, respectively; relative risk (RR) 0.97; 95% CI 0.61-1.53) [57].…”
Section: Vitamin D Supplementation and Preeclampsia Riskcontrasting
confidence: 70%
“…However, other meta-analyses of interventional studies [53,54] and a further randomized control trial (RCT; VDAART study) [57] with more participants than in the previous meta-analysis, did not support previous results. The VDAART study (Vitamin D Antenatal Asthma Reduction Trial) in the United States including 408 placebo and 408 subjects receiving 4,400 UI vitamin D3 initiated early in pregnancy (10-18 weeks), did not find a reduction on the preeclampsia incidence (8.08 vs. 8.33%, respectively; relative risk (RR) 0.97; 95% CI 0.61-1.53) [57]. High levels of serum 25(OH)D were achieved on maternal plasma at delivery in the intervention group (39.2 ± 15.3 vs. 26.8 ± 10.7 ng/dL in the control group), yet the risk of preeclampsia was not lower.…”
Section: Vitamin D Supplementation and Preeclampsia Riskcontrasting
confidence: 70%
“…Yet, there are conflicting data as to whether vitamin D supplementation provides protection from the disorder [35][36][37][38][39][40]. Mirzakhani et al [41] reported the results of a planned secondary outcome from the Vitamin D Antenatal Asthma Reduction Trial involving 816 women among whom 67 (8.2%) developed PE. Secondary analysis was conducted to determine specifically whether vitamin D supplementation decreased the risk of PE and showed that while such a supplementation indeed increased serum vitamin D levels, it did not affect the risk of PE.…”
Section: Implications For Practicementioning
confidence: 99%
“…In addition, the findings of the VDAART reported by Mirzakhani et al demonstrate a clear dose-response relationship between serum 25OHD levels and preeclampsia risk. The results of vitamin D supplementation trials with the goal of decreasing preeclampsia have largely been conflicting (15,18,20). Variations in trial design, including the vitamin D dose regimens, the timing during pregnancy in which the intervention was started, and the baseline vitamin D status of the subjects may account for the different observed effects on preeclampsia.…”
Section: Study Interpretation and Future Directionsmentioning
confidence: 99%
“…Currentplacebo-controlled clinical trial (clinicaltrials.gov NCT00920621) designed to evaluate vitamin D supplementation in addition to a daily multivitamin during pregnancy for the prevention of asthma or recurrent wheeze in offspring born to women or a biologic father with asthma, eczema, or allergic rhinitis (21). The group planned a secondary analysis to determine whether vitamin D supplementation also decreased the risk of preeclampsia (20). Mirzakhani and colleagues found that vitamin D supplementation during pregnancy increased serum vitamin D levels but did not affect the risk of preeclampsia.…”
Section: Study Interpretation and Future Directionsmentioning
confidence: 99%